Korelasi Self Control Dengan Prokrastinasi Akademik Mahasiswa semester Akhir Fakultas Dakwah Dan Komunikasi UIN Raden Fatah Palembang - Sriwijaya, R.M Putra; Razzaq, Abdur; Fitri, Hartika Utami (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This study entitled the relationship of self-control to academic procrastination in final semester students of the Faculty of Da'wah and Communication at UIN Raden Fatah Palembang. Academic procrastination is currently still found among students, especially final semester students who are in the process of working on their thesis. Academic procrastination can have a bad impact on students, because a lot of time is wasted and does not find useful results. This happens because of a person's lack of ability to control or change his inner response to avoid unexpected behavior. This study aims to determine the level and relationship of self-control to academic procrastination in final semester students of the Faculty of Da'wah and Communication at UIN Raden Fatah Palembang. This study uses a quantitative approach to the type of correlation research. The population in this study was 524 students and the sample was 52 respondents. The sample technique used is simple random sampling technique (random sampling), data collection techniques using a questionnaire (questionnaire) and documentation. Data processing techniques using SPSS Version 25 with product moment correlation. With a validity test level of 0.273 and a reliability test level of 0.6. The results showed that the level of self-control towards academic procrastination in final semester students was moderate. Judging from the acquisition of scores with moderate qualifications amounting to 59,61%. Meanwhile, for the level of academic procrastination, scores with moderate qualifications are as much as 69,23%. Then there is a significant relationship between self control and academic procrastination of final semester students with a relationship value of 0.458 using product moment correlation with a significance level of 5%. The results of this study indicate that there is a relationship between self-control and academic procrastination in final semester students